2015
DOI: 10.1111/tbed.12390
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Canine Parvovirus Strains Circulating in North-East China

Abstract: Canine parvovirus (CPV) is highly contagious and is a major cause of haemorrhagic enteritis and myocarditis in dogs. We investigated the genetic variation of emerging CPV strains by sequencing 64 CPV VP2 genes from 216 clinical samples of dogs from Heilongjiang, Jilin, Liaoning, Shandong and Hebei in 2014. Genetic analysis revealed that CPV-2b was predominant in Hebei and CPV-2a was predominant in the other four provinces. In addition, a CPV-2c strain has emerged in Shandong province. All samples had a Ser-Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 31 publications
5
54
2
Order By: Relevance
“…Whereas CPV‐2a and CPV‐2b are the prevalent variants circulating in Asia (Yi, Tong, Cheng, Song, & Cheng, ), and more recently, CPV‐2c has been described in the same continent (Chiang, Wu, Chiou, Chang, & Lin, ; Geng et al, ; Nakamura et al, ; Wang et al, ; Zhao et al, ; Zhou, Zeng, Zhang, & Li, ; Zhuang et al, ), showing molecular signatures different from those of other continents. Indeed, the Asian CPV‐2c variant shows specific amino acids in NS1 (60V, 544F, 545V, 630P) and VP2 (5A/G, 267Y, 297A, 324I, 370R) gene sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas CPV‐2a and CPV‐2b are the prevalent variants circulating in Asia (Yi, Tong, Cheng, Song, & Cheng, ), and more recently, CPV‐2c has been described in the same continent (Chiang, Wu, Chiou, Chang, & Lin, ; Geng et al, ; Nakamura et al, ; Wang et al, ; Zhao et al, ; Zhou, Zeng, Zhang, & Li, ; Zhuang et al, ), showing molecular signatures different from those of other continents. Indeed, the Asian CPV‐2c variant shows specific amino acids in NS1 (60V, 544F, 545V, 630P) and VP2 (5A/G, 267Y, 297A, 324I, 370R) gene sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Most recent Asian CPV strains exhibited four non‐synonymous nt changes that are responsible for aa substitutions Ala5Gly, Phe267Tyr, Tyr324Ile and Gln370Arg, and six synonymous nt changes (T135C, A207G, T101A, A732C, G1509A and A1659C) in the VP2 sequence (Table ). Change Tyr324Ile is predominant in recent Asian CPV strains (Yi et al., ; Geng et al., ; Zhao et al., ). In contrast, other changes have been observed only between 2013 and 2015 (Geng et al., ; Wang et al., ), and change Gln370Arg has been detected only in China in CPV strains from dogs and a strain from a giant panda (Guo et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…As most recent Asian CPVs, the Nigerian strains displayed other three aa substitutions in the VP2 sequence (F267Y, Y324I and Q370R). While change at aa residue 324 is predominant in all three CPV variants in Asia (Geng et al, ; Yi, Tong, Cheng, Song, & Cheng, ; Zhao et al, ; Zhou et al, ), the other changes have been less frequently observed, mainly in China since 2013, and change Q370R has been detected only in CPV‐2c strains (Geng et al, ; Guo et al, ; Mira, Purpari, et al, ; Mira, Purpari, Lorusso, et al, ; Wang et al, ; Zhuang et al, ). These aa substitutions are located in the greatest variable VP2 GH loop, comprised between aa 267 and 498, but while residue 267 is not exposed on the capsid surface (Chiang, Wu, Chiou, Chang, & Lin, ) and may not affect the antigenicity of CPV (Xu et al, ), residues 324 and 370 could have immunological implications or biological relevance.…”
Section: Discussionmentioning
confidence: 99%